ALAT PENIRIS MINYAK BERBASIS SMART BREAKER : UPAYA MENINGKATKAN PRODUKTIVITAS DAN KUALITAS PRODUK UMKM DI DESA CALUNG BUNGUR KABUPATEN LEBAK - Rahmatullah, Asep; Heryanto; Tripladi, Rizki; Aziz, Abdul; Friska, Indah; Rosita, Rika; Kusuma, Regita Putri; Faizurrohman, Rizqi; Azzahra, Siti Alivia (Jurnal JANATA, 2025)
Preliminary studies and observations conducted in Calung Bungur Village, Sajira District, Lebak Regency are known to have an area of 850 Ha with a total population of 3,240 people from 968 Heads of Families (KK). The greatest economic potential in Calung Bungur Village is in the agricultural and plantation sectors, where agricultural products are not only used for food security but also sold to mills, while plantation products are not only sold to collectors but also used as raw materials for home businesses by some people. However, the utilization of plantation products has not been processed optimally by the community. Therefore, a community service program will be implemented in collaboration with KKM-PkM Lecturers Group 64 Calung Bungur Village. The method of implementing activities uses the Participatory Rurral Appraisal (PRA) method which includes participatory counseling, socialization, and direct demonstration of tools. The results of the implementation of socialization activities and the application of appropriate technology for smart breaker-based oil spnnier machine to increase productivity and quality in cassava chips and banana chips MSMEs in Calung Bungur Village have been carried out well by providing real contributions in increasing knowledge, understanding and skills of the community which is marked by the active participation of the community and MSME actors as well as the rise of the entrepreneurial spirit as marked by the existence of new business pioneers by optimizing existing resources around Calung Bungur Village.